The cloud adoption playbook proven strategies for transforming your organization with the cloud - Abdula, Moe; Averdunk, Ingo; Barcia, Roland; Brown, Kyle; Emuchay, Ndu (John Wiley & Sons, Inc., 2018)
The essential roadmaps for enterprise cloud adoption As cloud technologies continue to challenge the fundamental understanding of how businesses work, smart companies are moving quickly to adapt to a changing set of rules.